Suvremeni trendovi razvoja telekomunikacija - Mikula, Miroslav; Šarić, Slavko (Promet - Traffic&Transportation, 2012)
The paper deals with modem telecommunications development trends. The authors first provide a review of major factors of impact upon this development (telecommunications users' needs, changes on the market of telecommunications services, and advancement of the telecommunications technology). In conclusion the paper lists some basic references of the future development of the telecommunications network in general and of the terminal equipment or facilities of this network in particular.